2012
DOI: 10.1111/j.1556-4029.2012.02183.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex Determination from the Second Cervical Vertebra: A Test of Wescott’s Method on a Modern American Sample*

Abstract: Numerous methods for establishing a biological profile exist; however, many of these methods rely on the recovery of several specific bones or on fragile skeletal elements that are sometimes irrecoverable. It is for this reason new methods utilizing other previously under-documented bones should be established and tested by the forensic anthropological community. This study tests the accuracy of Wescott's (J Forensic Sci 2000;45(2)) method for determining sex from the second cervical vertebra. Specimens were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 9 publications
(24 reference statements)
5
21
0
3
Order By: Relevance
“…In the present study the mean sagittal length of second cervical vertebrae was significantly (P<0.001) greater in male than that of female (p<0.001) which was similar to the study represented by Wescott 4 , Marlow 5 and Bethard 6 . The lowest sagittal length of second cervical vertebrae in male was greater than that of female.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the present study the mean sagittal length of second cervical vertebrae was significantly (P<0.001) greater in male than that of female (p<0.001) which was similar to the study represented by Wescott 4 , Marlow 5 and Bethard 6 . The lowest sagittal length of second cervical vertebrae in male was greater than that of female.…”
Section: Discussionsupporting
confidence: 90%
“…The tip of spinous process resembles an inverted U 1 . The sagittal length of second cervical vertebra is the difference between the most anterior point of the body and the most posterior point of the most projecting part of bifid spinous process [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors were able to identify sex from measurements taken from the second cervical vertebra at accuracy rates ranged from 70% to 92.9% (Bethard and Seet, 2013;Gama et al, 2015;Torimitsu et al, 2016;Wescott, 2000). Moreover they proved that the second cervical vertebra is a good sex identifier especially when bigger bones are damaged.…”
Section: Introductionmentioning
confidence: 99%
“…Several sex determination studies have been conducted by metric analysis of talus, femur, patella, humerus, calcaneus, metatarsals, tarsals, metacarpals, phalanges, scapula, clavicle, and sternum [9][10][11][12][13][14][15][16][17]. Other studies applied CT imaging and real bone subjects with different sample sizes and levels of accuracy for sex discrimination from the vertebra [3,[18][19][20][21][22][23]. Voisin et al showed that the useful sexually dimorphic bones for forensic sex estimation are the rst seven cervical vertebrae (C1-C7) [24].…”
Section: Introductionmentioning
confidence: 99%